1990
DOI: 10.1200/jco.1990.8.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of fluorouracil versus fluorouracil and high-dose continuous infusion leucovorin calcium for the treatment of advanced measurable colorectal cancer in patients previously unexposed to chemotherapy.

Abstract: Seventy-nine patients with advanced, measurable, metastatic colorectal cancer previously unexposed to chemotherapy were randomly assigned to treatment with either fluorouracil (FUra) administered intravenously at a dose of 370 mg/m2/d for 5 days or the combination of FUra in the same dose and schedule with high-dose continuous infusion leucovorin calcium (500 mg/m2/d) beginning 24 hours before the first dose of FUra and continuing for 12 hours after the completion of FUra therapy. Patients whose disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…The most consistently active agent for this disease has been 5-fluorouracil (5-FU), and most regimens have been based on this agent (Table 2). [17][18][19][20][21][22][23][24][25] Few studies, and certainly none of the most recent studies, have specifically examined the role of systemic chemotherapy for resectable liver disease. However, it is clear that for most chemotherapeutic regimens, less than one third of patients with liver metastases have shown any response.…”
Section: Results Of Medical Treatment Of Isolated Liver Metastatic DImentioning
confidence: 99%
“…The most consistently active agent for this disease has been 5-fluorouracil (5-FU), and most regimens have been based on this agent (Table 2). [17][18][19][20][21][22][23][24][25] Few studies, and certainly none of the most recent studies, have specifically examined the role of systemic chemotherapy for resectable liver disease. However, it is clear that for most chemotherapeutic regimens, less than one third of patients with liver metastases have shown any response.…”
Section: Results Of Medical Treatment Of Isolated Liver Metastatic DImentioning
confidence: 99%
“…Experimental studies have clearly established that the stabilisation of the ternary complex, and thus optimal TS inhibition, requires elevated cellular concentrations of CH 2 FH 4 (Danenberg and Danenberg, 1978;Houghton et al, 1981;Rustum et al, 1987;Keyomarsi and Moran, 1988;Chéradame et al, 1997a). Accordingly, clinical studies have demonstrated higher antitumour efficacy when FU is associated with folinic acid (FA), a precursor of CH 2 FH 4 Poon et al, 1989;Doroshow et al, 1990;Piedbois et al, 1992;Jäger et al, 1996). We previously closely studied the role of FA supplementation and CH 2 FH 4 intratumoral concentration on FU efficacy in a panel of 14 human cell lines (Chéradame et al, 1997a).…”
mentioning
confidence: 99%
“…TS forms a covalent ternary complex with an active metabolite of 5-FU, 5-fluoro-2'-deoxyuridine 5'-monophosphate (FdUMP), in the presence of the folate co-factor, 5,10-methylenetetrahydrofolate (CH 2 FH 4 ) (8). LV increases the intracellular level of CH 2 FH 4 in vitro (9,10) and in vivo (11,12), and potentiates the cytotoxicity of fluoropyrimidines (13,14) and their anticancer activity (15)(16)(17)(18). It should be noted, however, that the effect of LV on the efficacy of 5-FU is masked in conventional mouse xenograft models, since the folate pool is higher in mice fed a normal diet than it is in humans (19,20).…”
Section: Introductionmentioning
confidence: 92%